2013
DOI: 10.1080/09669582.2013.802325
|View full text |Cite
|
Sign up to set email alerts
|

DoesECOcertification deliver benefits? An empirical investigation of visitors’ perceptions of the importance ofECOcertification's attributes and of operators’ performance

Abstract: Certification is highlighted as a key sustainable tourism management tool. Yet, very little is known about visitors' perceptions of such schemes. This is an important gap: the success of certification schemes depends on consumers' confidence in the quality of products and services that the schemes endorse. This paper surveyed 610 visitors to the Wet Tropics World Heritage Area and surrounds in Queensland, Australia about (1) the perceived importance of various attributes of the ECO certification scheme; and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 61 publications
5
60
0
1
Order By: Relevance
“…The US travelers are already familiar with those ecolabels and perceive them to be relatively credible, which can positively influence their perceptions and behavior toward the brands associated with those ecolabels (Chan, 2013). Ecolabels could enhance not only lodging operations but also public perception, as the results of this study revealed that more than half (54.9%) of the participants perceive that the quality is better for accommodations with ecolabels than those without them, which is in line with the result by Esparon et al (2014).…”
Section: Discussion and Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…The US travelers are already familiar with those ecolabels and perceive them to be relatively credible, which can positively influence their perceptions and behavior toward the brands associated with those ecolabels (Chan, 2013). Ecolabels could enhance not only lodging operations but also public perception, as the results of this study revealed that more than half (54.9%) of the participants perceive that the quality is better for accommodations with ecolabels than those without them, which is in line with the result by Esparon et al (2014).…”
Section: Discussion and Limitationssupporting
confidence: 90%
“…Esparon et al (2014) found that visitors in Australia perceived hotels with eco-certification performing better than those hotels without it, in terms of conservation and marketing. In addition, travelers in New Zealand who are concerned about the environment have said that they would choose accommodations with ecolabels and would encourage others to use them (Fairweather et al, 2005).…”
Section: Research On Travelers and Ecolabelsmentioning
confidence: 97%
“…Oh, 2001;Ryan & Cessford, 2003), 2) relative measurement of attribute importance (Chen, 2014;H. Oh, 2001;Taplin, 2012aTaplin, , 2012b, 3) involving the performance of competitors (Chen, 2014;Esparon, Gyuris, & Stoeckl, 2014;Taplin, Figure 1. Importance-performance grid. importance and performance measurement is conducted in a relative manner, the needed variations in importance are provided and so this approach provides explicit validation of results and prevents misleading outcomes in IPA applications.…”
Section: Performance Measurementmentioning
confidence: 99%
“…By simultaneously looking at both, policy-makers and tourism marketers can identify which factors require the most attention and rectify them accordingly À the aim being to improve those values deemed highly important but which visitors have expressed dissatisfaction with, while also maintaining or enhancing core strengths (i.e. those values which are important and which visitors are satisfied with) (Angelova & Zekiri, 2011;Esparon, Gyuris, & Stoeckl, 2014). The relative importance of key GBRWHA-based values can also be understood by examining how they might be impacted by a particular change or management decision (e.g.…”
Section: Introductionmentioning
confidence: 99%